FACTORS AFFECTING THE ACADEMIC PERFORMANCE OF PRIMARY SCHOOL CHILDREN IN BASRAH CITY - Dr. Nawar H. Khalil; Dr.Narjis A.H.Ajeel (Scholar Express Journals, 2022)
Over the past decade, issues of child development and behavior have moved into prominent position in the mid stream of general medical care. As a sequence of increased awareness of the interrelationship of educational and health factors, educational professionals and parents have increasingly turned to pediatricians, general practitioners and otolaryngologists among others to consultation when problems arise in child’s learning or behaviour. This frequently takes the form of asking the physician to provide a simple etiology such as vision, hearing or speech problems, to explain the problem
Keywords: Academic Performance; school age; IQ test